Implementasi Manajemen Pendidikan Dalam Sarana Dan Prasarana - Dianita Rahayu Sukmawati; Roulina Magdalena Siburian; Nur Hidayatil Janah (Student Research Journal, 2023)
Student management in education which includes planning, organizing, controlling, and evaluating the learning process as well as managing student behavior. The main objective is to create an effective, inclusive, and supportive learning environment that promotes the holistic development of each student. Some of the principles of student management include goals that are aligned with school management, activities that support educational goals, building student unity, good mentoring, and encouraging student independence. The scope of student management includes analysis of student needs, student recruitment, student selection, student orientation, student grouping, student leadership and development, and registration and reporting. This document also discusses the importance of understanding the characteristics of each student, creating a safe and comfortable learning environment, facilitating effective learning, encouraging active participation, building positive relationships, developing social skills, leadership, and supporting students' holistic development.